The Consequences of Delaying Telling Children with Perinatal HIV About Their Diagnosis as Perceived by Healthcare Workers in the Eastern Cape; A Qualitative Study - Sphiwe Madiba; Cynthia Diko (MDPI AG, 2020)
Although the benefits of disclosure are considerable, informing children with perinatal HIV of their own HIV status is often delayed to late adolescence. This study examined the social and contextual challenges that influence delaying disclosure to children and assessed the outcomes of delayed disclosure on the psychosocial health of children as perceived by the healthcare workers (HCWs) providing care to these children. Data were collected from HCWs via focus group discussions. Nurses, lay counsellors, social workers, and dieticians were selected from facilities in a rural South African health district. Thematic analysis was performed. The caregivers' social context was the main barrier against informing children timely about their HIV diagnosis. The extent of the internalised HIV stigma influenced the delay in disclosing to the children. Delaying disclosure contributes to children's refusing to take their medication, leads to the accidental disclosure of HIV, give rise to anger and resentment towards the caregiver, increase the risk of secondary transmitting of HIV, and poor health outcomes. It is essential to train HCWs to support caregivers and children through the disclosure process to ensure that caregivers realise the benefits of disclosure. Strategies to encourage caregivers to disclose early should be sensitive to their concerns about the negative impacts of disclosure.